HISTORY AND DYNAMICS OF PONDOK PESANTREN MODERN DAAR AL ULUUM KISARAN DISTRICT ASAHAN - Ali Imran Sinaga; Hasan Matsum; Salman Ahyani (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
The objective of this research were to analyze: 1) The dynamics of educator in Modern Boarding School Daar Al Uluum Kisaran Asahan District, 2) The dynamics of students in Modern Boarding School Daar Al Uluum Kisaran Asahan District, 3) The dynamics of curriculum in Modern Boarding School Daar Al Uluum Kisaran Asahan District. The approach of this research was qualitative methods. The data obtained through interviews, observation and document. The Informant of this research was the Director of Islamic boarding school, Director Curriculum of Islamic boarding school, Director Administration of Islamic boarding school, headmaster of MTs, headmaster of MA, headmaster PKU, Adviser to the Asahan regency Indonesia islamic boarding school Majelis Ulama and others. The result of this research showed that: 1) The dynamic of educator in boarding school initially, the teaching staff at the boarding school were only buya or ummi who taught at Madrasah Tsanawiyah, Madrasah Aliyah in 1979, but since the opening of the Madrasah Aliyah Religious program in 1999, the teaching force at this boarding school has continued to increase, and now the number of educators has reached 111 people. 2) The Students at the boarding school in the beginning of its establishment experienced an increase and the highest glory was 3000 students in 2000, in 2007 decreased by 1500 students, and now the number continues to decline 760 students. 3) There are three curricula used in this boarding school, namely the Tahfizh curriculum which is implemented using the tasmi’ and muraja’ah methods, while the National curriculum is a curriculum that is applied nationally throughout Indonesia such as  K.13 and the boarding school curriculum, which is all student activities for 24 hours at the boarding school, along with teaching classical books.